ANALYSIS OF SYNCHRONOUS MOTOR EXCITATION SYSTEMS - Narkhojaeva, N.N.; Kamalov, N.K. (Educational Research in Universal Sciences, 2023)
At present, to regulate the excitation current of synchronous electric motors at industrial enterprises, mainly static (usually thyristor) and brushless excitation systems are used. Circuits with a DC generator on the shaft of a synchronous motor (SM) are currently practically not used.